Preferensi Konsumen Terhadap Keputusan Pembelian Beras pada Pasar Tradisional di Kabupaten Sambas - Sari, Dian; Novita, Uray Dian (Universitas Galuh, 2026)
Sambas Regency is one of the rice producing areas in West Kalimantan with a fairly high rice production. However, the dynamics of consumer behavior in choosing and purchasing rice, especially in traditional markets, have not been studied scientifically. Amidst competition between local rice and rice from outside the region, understanding consumer preferences is important to support the sustainability of the local rice market and the formulation of food distribution policies. This study aims to identify consumer preferences in rice purchasing decisions in traditional markets in Sambas Regency. This study was conducted using a survey method. Samples were taken using accidental sampling from 100 rice consumers in traditional markets in Sambas Regency. Data processing was carried out descriptively, using Fishbein's multi-attribute analysis. Based on the results of the study, it was concluded that the stages of the rice purchasing decision process in traditional markets in Sambas Regency go through the stages of recognizing needs, gathering information, evaluating alternatives, and making purchasing decisions. The main attributes considered in consumer preferences related to rice purchases in traditional markets in Sambas Regency are price, color, and package size, while aroma, texture, and shape have a relatively lower influence.